2011
DOI: 10.1097/mej.0b013e32833f212b
|View full text |Cite
|
Sign up to set email alerts
|

The utility of shock index in differentiating major from minor injury

Abstract: The SI can be a valuable tool, raising suspicion when it is abnormal even when other parameters are not, but is far too insensitive for use as a screening device to rule out disease. A normal SI should not lower the suspicion of major injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 22 publications
0
24
0
1
Order By: Relevance
“…Contrary to this hypothesis, we found that the SI was paradoxically lower in LT subjects at any relative reduction in central blood volume compared with that of the HT subjects. Although issues of inconsistent sensitivity in the use of the SI have been suggested based on uncontrolled clinical studies, 1,8,9 we conducted the present investigation using a human experimental model that allowed us to systematically control the progressive loss of central blood volume to the point of cardiovascular decompensation. Our results are consistent with clinical reports in supporting the notion that the SI lacks sensitivity, particularly at low levels of central hypovolemia, in its capacity to identify impending hemodynamic instability in those individuals most at risk for early development of decompensation (e.g., early decompensatory phase of shock).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to this hypothesis, we found that the SI was paradoxically lower in LT subjects at any relative reduction in central blood volume compared with that of the HT subjects. Although issues of inconsistent sensitivity in the use of the SI have been suggested based on uncontrolled clinical studies, 1,8,9 we conducted the present investigation using a human experimental model that allowed us to systematically control the progressive loss of central blood volume to the point of cardiovascular decompensation. Our results are consistent with clinical reports in supporting the notion that the SI lacks sensitivity, particularly at low levels of central hypovolemia, in its capacity to identify impending hemodynamic instability in those individuals most at risk for early development of decompensation (e.g., early decompensatory phase of shock).…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing and the potential benefits of SI as a predictor of mortality and Intensive Care Unit (ICU) admission was evaluated by many other studies as well, and its superiority to conventional vital sign measurements were demonstrated in most of them in pre-hospital and in-hospital settings in trauma and medical patients [20][21][22][23]. However, No study has yet focused on evaluating all of these indices (SI, MSI, and Age SI) in one patient population and comparing them with conventional vital sign measurement and with each other in a specific subgroup of triaged patients.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Elevated SI has also been shown to predict mortality [2,6,10,11] and need for critical care [10,[12][13][14][15][16] in adults. Studies in children have conflicting results with trauma studies showing an SI predictive of hemorrhagic shock [17] and a composite measure of trauma outcomes [18] with a few SI studies finding no predictive value [19][20][21].…”
Section: Introductionmentioning
confidence: 95%